Design of Laptop Computer Antenna for Wi-Fi 6E Band - Chung-Hao Huang; Ying-Chao Hong; Sen-Yu Liao; Yi-Chi Chen (Engineering Proceedings)
We propose a multiple-input multiple-output (MIMO) multi-band antenna for the WiFi-6E band. The planar size of the proposed antenna is 40 × 7.6 mm2, and it is built on a FR4 substrate with a thickness of 0.8 mm. By utilizing a 3 × 3.8 mm2 L-shaped parasitic element, additional resonant modes are introduced through coupling and resonance. The operating frequency bands are WLAN 2.4 GHz (2.4–2.8 GHz) and Wi-Fi 6E (5.06–7.13 GHz). The average antenna gain is 4.2 dBi, with an envelope correlation coefficient (ECC) less than 0.020 and a radiation efficiency between 70% and 92%.